Question 26: Simplify the Boolean expression (A + B)(A' + C).
Solution: AC + A'B
- Using the Distributive Law: (A + B)(A' + C) = AA' + AC + BA' + BC.
- Simplifying: 0 + AC + A'B = AC + A'B.
Question 27: Simplify the Boolean expression A + A'B'.
Solution: A + B'
- Using the Distributive Law: A + A'B' = A + B'.
Question 28: Simplify the Boolean expression A'B + AB'.
Solution: A ⊕ B
- This is the standard XOR expression: A ⊕ B = A'B + AB'.
Question 29: Prove that A * A' = 0.
Solution: 0
- This is the Complement Law in Boolean algebra: A * A' = 0, as a variable ANDed with its complement is always 0.
Question 30: Prove that A + A' = 1.
Solution: 1
- This is the Complement Law in Boolean algebra: A + A' = 1, as a variable ORed with its complement is always 1.
Question 31: Simplify the Boolean expression A + AB + A'B'.
Solution: A + B'
- Using the Distributive Law: A + AB + A'B' = A + B'.
Question 32: Simplify the Boolean expression A'B + A'B'.
Solution: A'
- Using the Distributive Law: A'B + A'B' = A'(B + B').
- Since B + B' = 1, the expression simplifies to A'.
Question 33: Simplify the Boolean expression AB + AB'.
Solution: A
- Using the Distributive Law: AB + AB' = A(B + B').
- Since B + B' = 1, the expression simplifies to A.
Question 34: Simplify the Boolean expression A(A' + B)(A + B').
Solution: AB'
- Using the Distributive Law: A(A' + B)(A + B') = A(A + B')(A' + B).
- Simplifying: A(A + B')(A' + B) = A * AB' = AB'.
Question 35: Simplify the Boolean expression A'B' + AB + A'B.
Solution: B + A'
- Group terms: (A'B' + A'B) + AB = A'(B' + B) + AB = A' + AB.
- Using Absorption Law: A' + AB = A' + B.
Question 36: Simplify the Boolean expression (A + B')(A' + B').
Solution: B'
- Using the Distributive Law: (A + B')(A' + B') = A(A' + B') + B'(A' + B').
- Simplifying: A'B' + A'B = A' + B'.
Question 37: Simplify the Boolean expression A(B + C') + A'B.
Solution: B + AC'
- Using the Distributive Law: A(B + C') + A'B = AB + AC' + A'B.
- Group terms: (AB + A'B) + AC' = B(A + A') + AC'.
- Simplifying: B + AC'.
Question 38: Simplify the Boolean expression A + (A'B)' + A'C.
Solution: A + B + C
- Using De Morgan's Law: A + (A'B)' = A + A + B = A + B.
- Thus, A + B + A'C simplifies to A + B + C.
Question 39: Simplify the Boolean expression A + A'B + A'B'.
Solution: A + B'
- Group terms: A + A'B + A'B' = A + A'(B + B').
- Since B + B' = 1, the expression simplifies to A + A' = A.
Question 40: Simplify the Boolean expression (A + B)(A' + B).
Solution: A + B
- Using the Distributive Law: (A + B)(A' + B) = AA' + AB + A'B + BB.
- Simplifying: 0 + AB + A'B + B = A + B.
Question 41: Simplify the Boolean expression (A + B')(A + C').
Solution: A + B'C'
- Using the Distributive Law: (A + B')(A + C') = A(A + C') + B'(A + C').
- Simplifying: A + B'C'.